Fairness Perceptions of the Division of Household Labor: Housework and Childcare. (March 2022) - Koster, Tara; Poortman, Anne-Rigt; van der Lippe, Tanja; Kleingeld, Pauline
An unequal division of housework has been found to be often regarded as fair, which may explain why women still do most household labor. This study extends previous research by also investigating childcare—an increasingly important part of household labor, which is likely to have a different meaning than housework. It examines how perceptions of fairness for both housework and childcare are influenced by the division of housework, childcare, and paid labor, and whether patterns differ by gender. Data from the Netherlands (men: N = 462; women: N = 638) show that unequal divisions of housework, and especially childcare, are often perceived as fair. When it comes to how an increasingly unequal household labor division is related to unfairness, associations are stronger for women than for men. Fairness of the household labor division is evaluated in relation to total workload and not in isolation from other types of labor.